Mengelola Glokalisasi: Menelusuri Dinamika, Transformasi, dan Tantangan Pangan di Sulawesi Selatan - Muhammad Anas; Faisal Akbar Zaenal; Lily Dianafitry Hasan (Politeknik Pariwisata Makassar, 2023)
This study explores South Sulawesi's glocalisation. This study is conducted in Makassar City, Pare-Pare City, and Bulukumba Regency due to their higher urban and tourism context mobilisation, port accessibility, and port potential. This study investigates using phenomenology. Document analyses, observations, in-depth interviews, and focus group discussions (FGD) contribute to carefully selecting culinary or tourism industry experts as informants. According to the research, globalisation and localisation have affected South Sulawesi dishes' appearance, aroma, flavour, and environment (sight and touch). Since these are commercial dishes, fundamental ingredients and market values are essential. Since